Anomalous left coronary artery from pulmonary artery repair: Outcomes from the European Congenital Heart Surgeons Association Database. Issue 6 (2nd March 2021) - Triglia, Laura Torlai; Guariento, Alvise; Zanotto, Lorenza; Zanotto, Lucia; Cattapan, Claudia; Hu, Renjie; Zhang, Haibo; Herbst, Claudia; Hörer, Jurgen; Sarris, George; Ebels, Tjark; Maruszewski, Bohdan; et al.
Abstract: Introduction: We sought to determine the surgical outcomes of patients with anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) enrolled in the European Congenital Heart Surgeons Association (ECHSA) database. Materials and Methods: From 1999 to 2019, 907 patients with ALCAPA underwent surgical repair and were included in the current study. The primary outcome was in‐hospital mortality. Secondary outcomes included frequency and results of concomitant mitral valve surgery and postoperative mechanical circulatory support (MCS). Results: The overall in‐hospital mortality was 6% (54/907) and was significantly higher in neonates ( p  = .01), patients with lower body surface area (BSA) ( p  = .01), and those requiring postoperative MCS ( p  = .001). Associated mitral valve surgery was performed in 144 patients (15.9%) and was associated with longer cardiopulmonary bypass (CPB) and aortic cross‐clamp times (AOX) ( p  ≤ .0001) but was not significantly related to an increase in in‐hospital mortality. Postoperative MCS was required in 66 patients (7.3%). These patients were younger ( p  ≤ .001), had a lower BSA ( p  ≤ .001), and required a longer CPB ( p  ≤ .001) and AOX time ( p  ≤ .001). Conclusions: ALCAPA repair can be achieved successfully, and with low surgical risk. Concomitant mitral valve procedures can be performed without increasing operative mortality. The use of MCS remains a valuable option, especially in younger patients.